2009
DOI: 10.4037/ajcc2009110
|View full text |Cite
|
Sign up to set email alerts
|

Aeromonas Septicemia After Medicinal Leech Use Following Replantation of Severed Digits

Abstract: Medicinal leeches are used to control venous congestion. Aeromonas in the leech gut are essential for digestion of blood. This case report describes a patient who had Aeromonas bacteremia develop after leeching. He had an injury to his hand that required replantation of his thumb. Following the surgery, leech therapy was started with ampicillin-sulbactam prophylaxis. Sepsis developed. Blood cultures were positive for Aeromonas that were resistant to ampicillinsulbactam. The antibiotic was changed to ciprofloxa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…These infections can require extended course of intravenous antibiotics via central venous access . Sepsis from Aeromonas infection has been reported after replantation . If leeches are utilized, appropriate antibiotic coverage is mandatory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These infections can require extended course of intravenous antibiotics via central venous access . Sepsis from Aeromonas infection has been reported after replantation . If leeches are utilized, appropriate antibiotic coverage is mandatory.…”
Section: Discussionmentioning
confidence: 99%
“…29 Sepsis from Aeromonas infection has been reported after replantation. 30 If leeches are utilized, appropriate antibiotic coverage is mandatory. All patients in our cohort were administered appropriate prophylactic antibiotic therapy at the time of leech therapy initiation.…”
Section: Discussionmentioning
confidence: 99%
“…of colonies per leech -SD anaerobic bacteria which are potentially pathogenic to human beings [6][7][8][9]15]. Clinical observations demonstrate that the endosymbiotic flora of the leech is capable of transmission into the patient during attachment and feeding [6].…”
Section: Discussionmentioning
confidence: 99%
“…Levine et al, reported a case of Aeromonas hydrophila septicemia after leech therapy, which was resistant to standard prophylactic antibiotic therapy (16). …”
Section: Discussionmentioning
confidence: 99%